The influence of mothers' parenting practices on adolescents in two social contexts - Lin, Kuei-Hsiu (2002)
Despite impressive evidence on the efficacy of the authoritative parenting style, we do not fully understand why or how it affects children. In this paper, I investigated how parenting practices influence child development by various measures of parenting behavior and included various functional forms (i.e., linear, interactive, and curvilinear effects). I analyzed two panel data sets, the Iowa Youth and Family Project (IYFP, n = 419) collected in Iowa in the United States, and the Taipei project (n = 973) conducted in Taipei, Taiwan. The equivalence of the relationship between parenting practices measured in the first year and adolescent delinquency and depression one year later was tested using youths from two distinct cultural backgrounds. To ensure the equivalence of the measurement, we used the structural equation modeling (SEM) technique. However, the SEM methods proposed for nonlinear effects suffer from several difficulties. Thus, the classic regression analysis for interaction and quadratic effects was used instead.;Basically, positive parenting practices (i.e., warmth/support, monitoring, inductive reasoning, and communication) were negatively related to delinquency and depression. In contrast, negative parenting behaviors (i.e., inconsistency, and corporal punishment) were positively related to delinquency and depression. Most models showed that the associations between parenting practices and adolescent depression and delinquency were the same across cultures. Few significant interaction and quadratic models were found. However, the effect sizes tended to be small